Effect of nattokinase on the pathological conditions in streptozotocin induced diabetic rats - Moe Yamaguchi; Ryo Fukuyama; Mitsugu Fujita (Heliyon, 2024)
Nattokinase (NK), also known as subtilisin NAT (EC 3.4.21.62), is a serine protease produced by Bacillus subtilis natto that has anti-inflammatory and fibrinolytic properties. To study whether NK prevents the progression of pathological changes in diabetes as an inflammatory disease, we examined the effect of NK on pathological conditions in streptozotocin (STZ)-induced diabetic rats using the following parameters: fasting blood glucose (glucose), total plasma protein (TP), creatinine, histopathology of renal corpuscles and tubules, advanced glycation end products (AGEs), and C-reactive protein (CRP). STZ-administered rats were maintained on a basic diet (CE-2) as control, low-NK diet (containing 0.2 mg NK/g diet), and high-NK diet (0.6 mg NK/g diet) for 14 days. High-dose NK significantly inhibited both glycogen deposition in the renal tubules and increase in the circulating AGE levels without downregulating glucose levels. Compared with the control group, the group treated with the high-NK diet presented a significant inhibition of the increase in the circulating CRP level on day 7 after the beginning of the treatment. However, the CRP level in the NK-H group reached the same level as that in the control group on Day 14. AGEs are known to induce CRP expression in hepatocytes, but the increase in CRP levels in our animal model was independent on the circulating AGE levels. In contrast, low-dose NK did not suppress changes in these parameters. Our present study suggests that NK suppresses glycogen deposition in renal tubules in a dose-dependent manner by the downregulation of AGE formation under hyperglycaemia in the rats with STZ-induced short-term diabetes. However, it is unclear whether this downregulation is caused by intact NK or peptides derived from NK during its digestion in the digestive tract.